Un apporto linguistico alla questione etrusca Il pronome "enan" e i suoi affini - Canuti, Massimiliano (2022)
In this paper is proposed the indefinite pronoun « nobody » like translation of the Etruscan word enan. This issue is pursuit by Linguistics analysis and data from historic and literary sources. An Etruscan negation schema, finally, explains the origin of enan.
Keywords: Etruscan; Negation; Syntax; Semantics; Typology